Recombinant canine stromelysin 3 inhibits drug induced apoptosis in vitro - KUMAR, B V SUNIL; KATARIA, MEENA; MURTHY, REDDI V V S N; SAXENA, MEETA; SHARMA, BHASKAR (The Indian Journal of Animal Sciences, 2015)
Matrix metalloproteinases (MMPs) are zinc metalloproteases having a pivotal role in extracellular matrix degradation, tumor growth, apoptosis, angiogenesis, invasion, and development of metastases. Stromelysin 3 (ST3) increased tumor take by suppressing cell apoptosis. Our present goal was to set up an in vitro model in which we could study this new function of ST3. For this purpose, we analysed effect of vinblastine, an anti-cancer drug, on ST3 treated MDCK (Madin-Darby canine kidney) cells. We found a marked decrease in the percentage of vinblastine induced MDCK cell death when the cells were pre-treated with recombinant ST3 as assessed by FACS analysis. Our data confirmed and extended the anti-apoptotic function of ST3 in-vitro.